Pola tingkah laku kewangan pekerja keluarga dwikerjaya. - Masud, Jariah; Haron, Sharifah Azizah; Othman, Mumtazah; Ramli, Zaimah (Malaysian Consumer and Family Economics Association, 2010)
In order to enhance the empowerment of consumerism, financial behaviours among workers are very important. Excellent financial behaviours will encourage individuals to achieve a high financial well-being. Previous reviews have that financial behaviour had a significant relation with financial well-being. The objectives of this study are to identify the pattern of financial behaviour among workers of dual-career families and to examine the differences in term of gender, education level and job position. The subjects of this study were government staff of different job positions. Based on this 'drop and pick-up' method, a total of 415 respondents were selected. The study findings showed that approximately 60 percent of respondents spent more than their income, more than 50 percent of respondents paid their utilities bill on time, and around 40 percent of respondent had some forms of saving. The overall level of financial behaviour practices were high, except for record keeping on expenses and saving for retirement. In addition, the differences in education level and job position are observed in the overall score of financial behaviour.